The Effect of Marketing Mix for Logistics Services on User Decisions in Manado (Case Study of PT. Pos Indonesia Logistics) - Stanss Levynna Hermien Verronica Joyce Lapian; Daniel Stefanus Imanuel Sondakh; Agnes Lutherani Ch. P. Lapian; Lis M Yapanto (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
Services is very important in this digital era. The decision to use logistics services is influenced by the 7 P's. The marketing mix is ​​one of the important aspects of marketing related to consumer purchasing decisions and is divided into product, price, promotion, location, people/HR (people), physical evidence and process. This research specifically aims to: (1) Know the characteristics of Indonesian Postal Logistics consumers. (2) Knowing what factors influence consumer purchasing decisions for Indonesian Logistics Post products. (3) Knowing the implementation of the marketing mix strategy at the Indonesian Logistics Post.This goal can be achieved by applying a series of explanatory research procedures where data collection is carried out in the city of Manado and the unit of analysis is the customers/consumers of postal logistics services. After the data is obtained then the data is processed and analyzed using multiple regression analysis, t-test and F-test. From the results of the regression analysis and hypothesis testing, it is obtained that the Product, Place, Promotion, People, Physical evidence and Process variables have a positive effect on consumer purchasing decisions (Buying decisions) at the logistics company PT. Logistics Post. If these variables increase, the buying decision will also increase. Vice versa. However, specifically for the Price variable, it shows a negative value, which means that the effect of the Price variable on the Buying decision is opposite, that is, if there is an increase in the price of PT. Post Logistics, there will be a decrease in purchasing decisions for these logistics products/services. Price is one of the determinants of consumers in determining a purchase decision for a product or service. Therefore consumers will definitely consider the price of an item or service with consumer income, the quality obtained and the benefits obtained. PT. Postal Logistics is assessed by the public as still selling its services at a higher price than its competitors. Responding to the conditions for logistics challenges in Indonesia, Post Logistik must be able to elaborate on the company's ability to provide solutions through a national approach that is synergized with global solutions for the use of the right technology, so that the logistics services offered do not only provide solutions for customers but also provide benefits to investors. in improving the Indonesian economy. Therefore a business model that can be built in order to produce competitive logistics service products is as follows: (1) Strategic cooperation with external parties to produce strategic partnerships in the field of transportation in order to realize excellent operations in the distribution function (moving goods) end to end. (2) Regular collaboration with external parties on the principle of a win-win solution to support supporting operations in the fields of Banking, Insurance, Information Technology and Trade. (3) Application of the 7P marketing mix principles (Product, Price, Place, Promotion, People, Physical evidence and Process). (4) Generate competitive postal logistics service offerings. (5) Based everything on the applicable government regulations.